Spatiotemporal responses to a rural highway by four mammal species - Brett, Caitlin K.; Mehner, Anna R.; Young, John H.; Lehnen, Sarah E.; Kline, Richard J. (Frontiers in Ecology and Evolution, 2025)
Roads can negatively impact the wildlife communities they transect. Road mortalities from wildlife-vehicle collisions are one direct effect, but roads may also indirectly affect wildlife behavior, movement, or local distribution. Quantifying the spatial extent of these road-effects is important for understanding how roads indirectly affect species of concern, identifying potential sources of disturbance, and for estimating the effectiveness of road mitigation structures. Farm-to-Market Road (FM)106, which transects part of the Laguna Atascosa National Wildlife Refuge in Cameron County, Texas, has been identified as a potential source of wildlife road mortalities, particularly for one of the two remaining breeding populations of ocelots (Leopardus pardalis) in the United States. Wildlife crossing structures (WCS) have been constructed on FM106 to mitigate these losses, however, the indirect effects of FM106 on wildlife have not yet been investigated. This study used camera trap arrays to quantify activity surrounding FM106 for four mammal species. Within each species, activity patterns were compared at roadside versus habitat reference sites to identify if proximity to the road significantly impacted the temporal distribution of target species throughout a typical day-night cycle. Temporal road avoidance, quantified as shifts towards more nocturnal activity at roadside sites, was seen for bobcat (Lynx rufus; p=0.04), coyote (Canis latrans; p=0.01), and white-tailed deer (Odocoileus virginianus; p<0.001), but not for striped skunk (Mephitis mephitis). Spatial distribution was also quantified for each of these species by modeling detection data at varying distances to FM106 while also considering the influence of vegetation and other landscape factors. Bobcats and coyotes displayed a limited degree of attractance to the roadside whereas white-tailed deer and skunks seemed unaffected by proximity to the road. These results indicate that while there may be advantages to accessing roadside sites (e.g., scavenging, hunting, or travel opportunities), certain species tend to modify their daily movement behavior to selectively use these areas at times when vehicular traffic is at its lowest.